A Note on the Movement of some Indian Timbers - Jain, V. K.; Arora, K. L.; Sharma, A. K. (Indian Forester, 1993)
’Movement’ is the term applied to shrinkage or swelling of seasoned wood in service due to fluctuations in atmospheric conditions. In this paper experimentally determined movement values of 6 Indian species between 32 and 93 per cent R.H. are reported. Amongst the limited number of species studied, teak showed the smallest movement value whereas Eucalyptus showed the largest movement value.